B cell‐derived circulating granzyme B is a feature of acute infectious mononucleosis. Issue 6 (26th June 2015) - Hagn, Magdalena; Panikkar, Archana; Smith, Corey; Balfour, Henry H; Khanna, Rajiv; Voskoboinik, Ilia; Trapani, Joseph A
Abstract : Granzyme B (GzmB) is a serine protease best known for inducing target cell apoptosis when released by cytotoxic T lymphocytes (CTLs) or natural killer cells with pore‐forming perforin. As a result, GzmB detected in the serum of virus‐infected individuals has typically been attributed to these sources. Here, we show that patients with recently diagnosed infectious mononucleosis caused by Epstein‐Barr virus (EBV) have high circulating levels of GzmB that may be derived from infected B cells early in course of disease. We recently reported that human B cells from healthy donors secrete active GzmB when stimulated in vitro through B‐cell receptor (BCR) ligation and interleukin (IL)‐21. We found that infecting B cells with EBV greatly amplified GzmB secretion in response to the same stimuli, but the expression was terminated once the infection had become latent. Our results represent a rare instance of GzmB expression by non‐CTL/natural killer cells in the context of infection with a human pathogen. Infectious mononucleosis: A defensive enzyme from B‐cells: A novel source of the cell‐killing enzyme granzyme B has been found in patients with acute infectious mononucleosis (glandular fever). The enzyme is already known to be released by T‐cells and natural killer cells of the immune system as part of the body's response to virus infection. Infectious mononucleosis is caused by infection with Epstein‐Barr virus (EBV). Joseph Trapani of the Peter MacCallum Cancer Centre in Melbourne, Australia, and co‐workers in Australia and the USA investigated the origin of granzyme B in the blood of recently diagnosed patients. The research suggests that granzyme B may be produced by B‐cells of the immune system infected with EBV. The identification of this unexpected source of the enzyme should assist understanding of infectious mononucleosis and also the role of granzyme B in virus infection in general.